Networking Magic: Andrew Lang and the Science of Self-Interest - Rajan, Supritha (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
This article examines Andrew Lang’s anthropological writings on magic and religion in relation to a broader network of literary and sociological discourses. Lang’s work, along with that of others, highlights the labors nineteenth-century anthropologists expended to segregate magic from science, religion, and utilitarian action in the capitalist public sphere. Despite such efforts at segregation, however, nineteenth-century anthropological writings expose the genealogical continuities between magic, science, religion, and self-interest. These continuities, the essay contends, also surface in anthropology’s sibling discourses: literature and political economy. Lang’s contemporaries, such as H. Rider Haggard and Thomas Hardy, drew on anthropological findings in their fictional representations of magical rites and beliefs either in rural Britain or at the colonial periphery. Magic’s proximity to science, religion, and capitalist self-interest also undergirds Herbert Spencer’s systems theories and reverberates in the political economists that drew on Spencer’s work. The essay thus demonstrates not only how Lang functions as a node within a broad disciplinary network, but also how the concept of magic traverses numerous discursive fields.